Constructing Policy Contributions from Critiques: Two Examples from Research into Australian Care Work - Jefferson, Therese (Springer, 2013)
In common usage, a critique is often understood as fault finding and can be associated with negative judgements. It is also undeniably the case that heterodoxy in economics has been closely associated with extensive and ongoing critiquing of mainstream economics for several decades, Frank Stilwell's body of work demonstrates the importance of linking critiques with contributions to policy discussion and applied research. The purpose of this chapter is to argue that critiques of mainstream economic theories can also provide a valuable resource for achieving outcomes such as impact and grant funding that are increasingly important to economists working in the higher education sector. This is argued with reference to two recent projects relevant to the wages and employment conditions of care workers in Australia. In both of these cases, the contributions of academic economists were centred on analyses of the inappropriate nature of mainstream economic assumptions for understanding key aspects of care work. Critiques of mainstream analysis provided a basis for identifying a need for different forms of data collection, analysis and policy development which could most usefully be undertaken by those who do not have an a priori commitment to the assumptions underpinning mainstream analyses. The conclusion is that targeted critiques can be a basis for positive contributions to the development of research agendas and policies relevant to key issues of economic equity in the Australian economy.